Data-driven LCA for green industrial innovation of custom curtain walls - Theo Zaffagnini; Luca Morganti (Agathón)
The optimization and advanced management of design, engineering, and building construction, aimed at the maximization of environmental performance, are among the innovations facilitated by the tools of the digital transition. In this context, this study focuses on and proposes the integration of peculiar IT data in the life cycle assessment of industrial products. The present paper also outlines the current limitations of Life Cycle Assessment practices concerning the prefabrication of custom modules for curtain walls and how these limitations can be overcome through a data-driven approach, integrated with specific platforms and software used by companies. The aim is to foster sustainable and resilient innovation, bridging the gap between information research, and industrial production and its organizational processes.